Деякі аспекти інформатизації в системі судочинства - Логінова, Наталія Іванівна; Логинова, Наталья Ивановна; Loginova, Natal'ja; Трофименко, Олена Григорівна; Трофименко, Елена Григорьевна; Trofimenko, Elena (My University, 2013)
The article examines the regulatory support of information in the justice system of Ukraine. The concepts “informatization” and “information support” was analyzed. The guidelines for the developments of information the courts were defined.
Логінова Н. І., Трофименко О. Г. Деякі аспекти інформатизації в системі судочинства / Н. І. Логінова, О. Г. Трофименко // Митна справа. - 2013. - Ч. 2. - Кн. 1. - С. 472-477.
Keywords: інформатизація; система судочинства; інформаційно-пошукові системи; інформаційне забезпечення; информатизация; система судопроизводства; информационно-поисковые системы; информационное обеспечение; informatization; justice system; information retrieval systems; information support